O descuido de se tombar: a importância da paisagem cultural dos engenhos de cachaça e rapadura como patrimônio do município de Areia - Ferreira, Anna Cristina Andrade (2010)
This study aims to investigate the importance of the city of Areia, Paraíba, as a cultural landscape formed by the junction of its urban and rural. The City of Areia is one of the newest urban sites to receive the title of National Heritage, with its tumbling approved in 2006, due to its historical, architectural, urban and landscape importance. If distinguished primarily by their location and urban expansion following the ridge of the Serra Borborema. However, the favored asset protection only to safeguard the urban core, with the landscape denying the "frame" of the city. However, what is perceived by reviewing the history of the city is the landscape, formed mainly by their rural area, especially the mills of cachaça and rapadura , sets up a cultural heritage as or more important than the urban. The growth and development of the city have been based on agriculture, and through different economic periods throughout its history: cotton, sugar cane, coffee, agave and cattle breeding, but out of all these crops, the sugar cane has behaved like that intermittent, never totally abandoned. Thus, were the engines of cachaça and rapadura which outlined its growth, influencing directly the social, economic, urban and cultural Areia, and strengthening its tradition as producing city of cachaça and rapadura . The set of different forms of assets that comprise the landscape of the mills - the architecture, environmental characteristics, the intangible heritage - assisted in the configuration and transformation of the landscape of the city, and urban and cultural characteristics. All these issues lead to reflect on the importance of the mills to the history and culture of the city and the need to promote their safeguarding, while important documents in preserving the cultural identity of Areia.